Endorsement of clinical practice guidelines by the Scandinavian Society of Anaesthesiology and Intensive Care Medicine. Issue 2 (3rd December 2018) - Rehn, Marius; Chew, Michelle S.; Olkkola, Klaus T.; Örn Sverrison, Kristinn; Yli‐Hankala, Arvi; Møller, Morten Hylander
Abstract: Clinical practice guidelines from other organizations or societies with assumed clinical and contextualized relevance for Scandinavian Society of Anaesthesiology and Intensive Care Medicine (SSAI) members, may trigger a formal evaluation by The Clinical Practice Committee (CPC) for possible SSAI endorsement. This avoids unnecessary duplicate processes and minimizes resource‐waste. Identified guidelines are assessed for endorsement using the Appraisal of Guidelines for REsearch and Evaluation (AGREE) II instrument. The SSAI CPC utilizes the AGREE II online coordinated group appraisal platform to assess the methodological rigor and transparency in which the guideline was developed. The results of the assessment, including the decision to endorse or not, are presented to the SSAI Board for sanctioning. This document briefly outlines the process for evaluation of non‐SSAI guidelines by the CPC for possible SSAI endorsement.